Adenocarcinoma of Ampulla of Vater Presented as Recurrent Jaundice - Jagtap, Sunil Vitthalrao; Jokhi, Cyrus Dhara; Patil, Digvijay; Jagtap, Swati S (Annals of Pathology and Laboratory Medicine, 2018)
Background Ampullary carcinoma are relatively uncommon neoplasm which approximately seen in 0.2% of gastrointestinal carcinomas. Clinically these patient generally present at an earlier stage of the disease. As their strategic location may cause early biliary obstruction. Case history A 70 year old male patient was presented with history of pain in abdomen, anorexia and repeated history of jaundice. On ultrasonography and CT scan abdomen-pelvis showed proliferative growth at periampullary area suggestive of ampullary malignancy. Associated cholelithiasis was noted. Patient underwent surgical treatment of pancreaticoduodenectomy with cholecystectomy. On histopathology revealed moderately differentiated intestinal type of adenocarcinoma of ampulla of Vater, Grade II. Conclusion We are presenting this uncommon neoplasm for its rarity, recently distinguished subtype on histopathology, clinical behavior and radiological findings.